SOROK-SNEZHNAYA BELT OF PLUMASITIC RARE-METAL GRANITE AND ASSOCIATED TIN-TUNGSTEN MINERALIZATION IN THE EASTERN SAYAN AND THE KHAMAR DABAN - Kozhenvikov O.K.; Perelyayev V.I. (My University, 1987)
Plumasitic rare-metal granites (PRMG) are alumina-rich, calcalkalic and subalkalic rocks of the lithium-fluorine geochemical type, with which tin, tungsten, molybdenum, beryllium, tantalum and fluoride mineralization is associated. The first finds of PRMG in the Eastern Sayan and the Khamar Daban were made at the beginning of the 1960's and in the middle of the 1970's. However, recent work has led to finds of new outcrops of PRMG, has produced information on the composition, internal structure and the attitude of their intrusions at different depths, the nature of the accompanying ore mineralization, and has placed such granite in the geologic history of their region. The resulting data have also allowed analysis of the distribution of PRMG here. Besides geologic data, information obtained in gravimetric surveys proved very useful for that purpose.